Analysis of epoxy composite with diapers waste as fillers: relationship of density, porosity and sound absorption coefficient - Mohd Fodzi, Muhammad Haikal; Marsi, Noraini; Shariff, Hafizuddin Hakim (IAEME Publication, 2020)
In this study, epoxy composites consisting of diapers waste (DW) as filler to improve the strength of the materials were produced by hand lay-up fabrication process. The inclusion of the DW significantly improves the sound absorption properties of epoxy composites. This study analyzes the relationship between the density, porosity and sound absorption coefficient properties of different weight ratio of the DW in the epoxy composites. Density and porosity is the key factor for acoustic efficiency determination in the same composite form. It can be mainly attributed to great number of voids which more porous and less dense into the matrix, increasing the sound absorption efficiency of the epoxy composites materials. The properties of the diapers waste are lightweight which show that, the incorporation of the diapers waste as fillers in the epoxy composite shows lower value of the density while increase in terms of porosity. Ratio 0.5 DW/epoxy had the most excellent properties in terms of lower density, higher porosity and sound absorption coefficient with 0.93 SAC score.